Vericiguat in combination with isosorbide mononitrate in patients with chronic coronary syndromes: The randomized, phase Ib, VISOR study - Michael Boettcher; Gerd Mikus; Dietmar Trenk; Hans‐Dirk Düngen; Frank Donath; Nikos Werner; Mahir Karakas; Nina Besche; Dominik Schulz‐Burck; Mireille Gerrits; James Hung; Corina Becker (Clinical and Translational Science, 2022)
Abstract Vericiguat was developed for the treatment of symptomatic chronic heart failure (HF) in adult patients with reduced ejection fraction who are stabilized after a recent decompensation event. Guidelines recommend long‐acting nitrates, such as isosorbide mononitrate, for angina prophylaxis in chronic coronary syndromes (CCS), common comorbidities in HF. This study evaluated safety, tolerability, and the pharmacodynamic (PD) interaction between co‐administered vericiguat and isosorbide mononitrate in patients with CCS. In this phase Ib, double‐blind, multicenter study, patients were randomized 2:1 to receive vericiguat plus isosorbide mononitrate (n = 28) or placebo plus isosorbide mononitrate (n = 13). Isosorbide mononitrate was uptitrated to a stable dose of 60 mg once daily, followed by co‐administration with vericiguat (uptitrated every 2 weeks from 2.5 mg to 5 mg and 10 mg) or placebo. Thirty‐five patients completed treatment (vericiguat, n = 23; placebo, n = 12). Mean baseline‐ and placebo‐adjusted vital signs showed reductions of 1.4–5.1 mmHg (systolic blood pressure) and 0.4–2.9 mmHg (diastolic blood pressure) and increases of 0.0–1.8 beats per minute (heart rate) with vericiguat plus isosorbide mononitrate. No consistent vericiguat dose‐dependent PD effects were noted. The incidence of adverse events (AEs) was 92.3% and 66.7% in the vericiguat and placebo groups, respectively, and most were mild in intensity. Blood pressure and heart rate changes observed with vericiguat plus isosorbide mononitrate were not considered clinically relevant. This combination was generally well‐tolerated. Concomitant use of vericiguat with isosorbide mononitrate is unlikely to cause significant AEs beyond those known for isosorbide mononitrate.